Dimensión ambiental en la formación profesional de los estudiantes de la Facultad de Educación de la Universidad Nacional de Huancavelica - Cóndor Salvatierra, Edwin Julio (Pontificia Universidad Católica del Perú. Fondo Editorial, 2018)
El estudio explica en qué medida se ha incorporado la dimensión ambiental en la formación profesional de los estudiantes de la Facultad de Educación de la Universidad Nacional de Huancavelica. Se utilizaron los métodos descriptivo y explicativo y se emplearon fichas de análisis de contenido y cuestionarios para el recojo de los datos. La población estuvo conformada por 72 docentes y 629 estudiantes. Se observó que la incorporación de la dimensión ambiental en el plan curricular es moderada; en cambio, la extensión universitaria y la proyección social son incipientes. Asimismo, la formación ambiental de los estudiantes es sólida.Finalmente, se concluyó que la incorporación de la dimensión ambiental en la formación profesional de los estudiantes es moderada; sin embargo, es necesario implementar acciones para su incorporación en la investigación, la extensión universitaria y la proyección social.

The study explains what extent the environmental dimension has been incorporated in the professional training of students of the Education Faculty of the National University of Huancavelica. The descriptive and explanatory methods were used and we used content analysis sheets and questionnaires to collect the data. The population consisted of 72 teachers and 629 students. The incorporation of the environmental dimension in the curricular plan is moderate. However, in research, university extension and social projection are incipient. In addition, the environmental education of the students is solid. Finally, was concluded that the incorporation of the environmental dimension in the professional training of the students is moderate; however, it is necessary to implement actions for its incorporation in the research, university extension and social projection.

The study explains what extent the environmental dimension has been incorporated in the professional training of students of the Education Faculty of the National University of Huancavelica. The descriptive and explanatory methods were used and we used content analysis sheets and questionnaires to collect the data. The population consisted of 72 teachers and 629 students. The incorporation of the environmental dimension in the curricular plan is moderate. However, in research, university extension and social projection are incipient. In addition, the environmental education of the students is solid. Finally, was concluded that the incorporation of the environmental dimension in the professional training of the students is moderate; however, it is necessary to implement actions for its incorporation in the research, university extension and social projection.
Environmental dimension in the professional training of the students of the Education Faculty of the National University of Huancavelica
Environmental dimension in the professional training of the students of the Education Faculty of the National University of Huancavelica
Keywords: Educación; https://purl.org/pe-repo/ocde/ford#5.03.00